Nahdlatul Ulama's Cultural Strategy Against Wahhabism and Radicalism and Its Impact on Islamic Education - Rahman, Mufiqur; Mo’tasim; Fahruddin, Ahmad Hanif; Masrufah; Rasuki (LETIGES, 2025)
This study explores the strategic role of Nahdlatul Ulama (NU) in suppressing Wahhabism and radicalism in Sumenep Regency through cultural and religious moderation initiatives. As Indonesia's largest Islamic organisation, NU serves as a vital civil society actor in preserving the country's pluralistic religious landscape, particularly in rural and archipelagic areas. Using a qualitative case study approach, data were collected through interviews, focus group discussions, observations, and document analysis involving NU leaders, educators, and government officials. The primary data consisted of field findings from participants, while secondary data included institutional documents, reports, and literature relevant to NU programs. Data were analysed using thematic analysis through interactive cycles of reduction, data display, and conclusion drawing. The findings reveal that NU Sumenep exercises agency by mapping radical-affiliated institutions, labelling mosques, launching ideological training for cadres (PKPNU), and promoting religious moderation through media and higher education networks. These initiatives represent a contextualised model of grassroots resistance to exclusivist ideologies. NU's agency, grounded in the Ahlussunnah wal Jama’ah tradition and aligned with national policy frameworks, contributes to ideological resilience and reinforces a moderate Islam that is inclusive, tolerant, and nationally committed. Furthermore, these efforts significantly influence Islamic education in Sumenep by strengthening curricula of religious moderation, shaping institutional identity in Islamic schools and pesantren, and providing preventive frameworks that reduce the penetration of Wahhabi-oriented teachings within educational environments.